2001
DOI: 10.1080/14636310120048065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Evaluation in Ensuring Excellence in Communications and Information Technology Initiatives

Abstract: This article presents an approach to the evaluation of communications and information technology (CIT) programmes in which the evaluation makes a positive contributio n to ensuring excellence in the programme. After a brief introductio n outlining changing attitude s to the commissioning of evaluations of CIT policy initiatives in the last 20 years, the article explores the politicise d purposes of evaluations , the kinds of knowledge that sponsors may be seeking, and the need for evaluations to use a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…NOF training, although largely welcomed by teachers, had areas for improvement, such as providing time for assimilation (OFSTED 2001). For example, the gender divide in confidence and perceived competence noted in 1998 had narrowed by 2001, but training should be evaluated with this in mind to ensure that ICT's potential for teaching and learning in communication and collaborative work is fully exploited (Somekh 2001).…”
Section: Resultsmentioning
confidence: 99%
“…NOF training, although largely welcomed by teachers, had areas for improvement, such as providing time for assimilation (OFSTED 2001). For example, the gender divide in confidence and perceived competence noted in 1998 had narrowed by 2001, but training should be evaluated with this in mind to ensure that ICT's potential for teaching and learning in communication and collaborative work is fully exploited (Somekh 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These are all higher orders of abstract thinking. Whether multimedia learning tools actually promote better learning outcomes at higher levels is an ongoing focus of research (Somekh, 2001;Anderson and Kanuka, 2003;Eysenbach, 2003). Until recently, there has been no established peer-review system for electronic learning objects, although there is good agreement on the need for one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the efficacy and quality of currently available programs vary widely (Kim et al, 2003). Therefore, as the demand for electronic education grows, so too does the demand for systematic evaluation so as to improve its quality (Somekh, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This fact is supported by Means and Olson [15] who noted that technology engaged students in challenging and authentic learning. Students from the treatment group have also asserted that they preferred computer simulations-based instruction over regular instruction; this finding lends support to Somekh [20] who has indeed highlighted that computer technology can provide strong visual elements that would be readily welcomed by teachers and students.…”
Section: Discussionmentioning
confidence: 65%
“…Data collected during the lessons in the treatment group have also indicated that the computer simulations were better appreciated than regular instruction by the students. Besides, all students of the treatment group have stated in the questionnaire that they have liked the visual effects provided by computer simulations; indeed, Somekh [20] has earlier reported that computer technology can provide strong visual elements that would be readily welcomed by teachers and students. In addition, Papert [21] has also stated that early exposure to science through visualization promotes independent learning by using the child's intrinsic curiosity, and by integrating science into his understanding of the world.…”
Section: Data Collected From Observation Checklists and Questionnairementioning
confidence: 99%